Optimization and Validation of a Multiplexed Luminex Assay To Quantify Antibodies to Neutralizing Epitopes on Human Papillomaviruses 6, 11, 16, and 18 - Dias, Dennis; Van Doren, Jeff; Schlottmann, Sonela; Kelly, Sheri; Puchalski, Derek; Ruiz, Wanda; Boerckel, Patricia; Kessler, Joseph; Antonello, Joseph M.; Green, Tina; Brown, Martha; Smith, Judith; et al. (Clinical and Diagnostic Laboratory Immunology, 2005)
Classifications Services CVI Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue CVI About CVI Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy CVI RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 1556-6811 Online ISSN: 1556-679X Copyright © 2014 by the American Society for Microbiology. For an alternate route to CVI .asm.org, visit: CVI